Hypoxic Ischemic Encephalopathy (HIE) in Term and Preterm Infants - Ristovska Sanja; Stomnaroska Damchevski, Orhideja; Danilovski Dragan (Macedonian Academy of Science and Arts/Sciendo, 2022)
Hypoxic-ischemic syndrome (HIS) and Hypoxic-ischemic encephalopathy (HIE) are conditions that affect term and premature babies, with different pathophysiology and different brain disorders. HIE appears in 1-6 / 1000 live births and 26/1000 live births in developing countries. 15-20% die in the early neonatal period, while surviving babies have severe neurological impairment, including cerebral palsy, epilepsy, visual and hearing impairment, cognitive impairment, intellectual, behavioural, and social disorders. The hypoxic-ischemic event occurs before, during or after birth. The reasons may be related to the mother, the way of birth, the placenta, and the newborn. The criteria for diagnosis of HIE include a combination of perinatal factors, the need for resuscitation, standard neurological examinations, neurophysiological monitoring, neuroimaging methods and biochemical markers. The most effective treatment for HIE is hypothermia in combination with pharmacological therapy. HIE and HIS are problem that still persist in developing countries due to inadequate obstetric care, neonatal resuscitation, and hypothermia. Current and emerging research for HIE examines new markers for early recognition, treatment, and appropriate neuroprotection of high-risk term and premature infants.
Keywords: Hypoxic-ischemic syndrome; hypoxic-ischemic encephalopathy; premature newborn; term newborn